The Specialist Dementia Care Program: Describing and evaluating a novel model of care for people with severe and intractable behaviors in Australia. (20th December 2022) - Morris, Thomas; Atee, Mustafa; Alford, Marie
Abstract: Background: A small proportion of people living with dementia experience very severe and intractable behaviors that cannot be supported by mainstream aged care. As a result, this population often rotates between acute, mental health, and aged care settings, and is at increased risk of inappropriate psychotropic prescribing and hospitalization. This led the Australian Government to announce in 2016 the funding for 35 Specialist Dementia Care Program Units (SDCPUs) across Australia. SDCPUs are purpose built, cottage‐like units staffed by specialist multidisciplinary teams who provide person‐centered care for people with very severe and intractable behaviors and psychological symptoms of dementia (BPSD). SDCPUs aim to reduce BPSD, improve quality of life, reduce inappropriate prescribing, and ultimately successfully transition residents to mainstream care within 12 months. As of January 2022, 10 SDCPUs were operational in 6 of 8 states and territories of Australia. Method: Eligibility criteria for admission to SDCPUs include: (1) a diagnosis of dementia; (2) evidence of very severe BPSD (e.g., physical aggression); (3) evidence that the behaviors are enduring (i.e., have lasted at least 3 months); and (4) evidence of intractability to adequate trials of treatment (e.g., nonpharmacological interventions). This session will describe and discuss this assessment process required to access SDCPUs in Australia, the design features and model of care required of their operation, as well as learnings from the first two years of their operation. Result: This session will also present the first longitudinal results of the impact of SDCPUs on resident behavior and wellbeing. Specifically, we will present the clinical outcomes of 37 residents from two SDCPUs, including BPSD, quality of life, activities of daily living, mood, prescribed psychotropics, rates of hospitalization, and successful transition into mainstream aged care. Conclusion: We will discuss these findings in the context of feasible and effective emerging models of care for BPSD support worldwide.